Assessing chemical contamination in the coastal waters of the Adriatic Sea using active mussel biomonitoring with Mytilus galloprovincialis. (April 2019) - Bajt, Oliver; Ramšak, Andreja; Milun, Vesna; Andral, Bruno; Romanelli, Giulia; Scarpato, Alfonso; Mitrić, Milena; Kupusović, Tarik; Kljajić, Zoran; Angelidis, Michael; Ҫullaj, Algi; Galgani, François
Abstract: The MYTIAD project focused on the assessment of chemical contamination (metals, PAHs, PCBs and organochlorine pesticides) in the Adriatic coastal waters by active mussel watching. Its purpose was harmonising and standardising strategies and methodologies used to assess the contamination status of the Adriatic Sea, in the framework of the WFD, the MSFD and UNEP/MAP Integrated Monitoring and Assessment Programme. Data on metals pointed out some hotspots along the eastern and western Adriatic Sea coasts, with the highest values of total PAH concentration detected in Split, Trieste, and Taranto (Ionian Sea). PCB and endrin contamination was higher in the Adriatic Sea than in the western Mediterranean Sea. This is the first comprehensive overview of contamination in the Adriatic Sea with critical comparisons of related studies over the Mediterranean Sea. It provides a useful harmonised dataset to support a coordinated definition of baselines, targets and thresholds, and further management of chemical contamination. Highlights: Results provide a harmonised dataset to support the coordinated management of chemical contamination in the Adriatic Sea. Concentrations of metals (Hg, Cd, Ni and Pb) are lower in the Adriatic Sea than in the Western Mediterranean Sea. PCB, DDTs and endrin are higher than in the Western Mediterranean Sea. PAHs are mostly of mixed origin, pyrogenic and petrogenic.